STRENGTHENING BUSINESS FOUNDATIONS: FINANCIAL STRATEGIES FOR SUSTAINABILITY - Loso Judijanto; Fina Diana, Ridwan (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
In the realm of business, financial strategy is essential to enhancing the sustainability and performance of an enterprise. It entails prudent money management to accomplish long-term objectives while preserving financial stability. In order to successfully apply this method, there are a few important concepts to comprehend. The importance of finance in business cannot be ignored. It provides a clear understanding of a company's cash flow, expenses, and revenues, and helps identify the financial resources needed to operate and grow. By understanding a company's financial health, business owners can make smarter decisions in allocating funds for investment, product development, or market expansion. The research was carried out using the literature study method. A literature review is used to collect data and information related to financial strategies for business sustainability. This research discusses the definition, components, benefits and sustainability of business, financial risk management in the context of sustainability, financial innovation for sustainability, the relationship between sustainability investment and financial performance, and financial strategies for business sustainability